Understanding the effect of virtual reality on anxiety and pain due to intrauterine device insertion - Herliana Riska; Rahayu Widaryanti; Istri Yuliani; Ester Ratnaningsih (Wolters Kluwer Medknow Publications, 2024)
Background: Virtual Reality (VR) can provide more interruption as it inundates the patient in a different universe and connects with numerous faculties. VR has been utilized to deal with the pain and stress associated with various painful medical procedures. Materials and Methods: This multi-method study was conducted on 60 women in an Intrauterine Device (IUD) acceptor. This research occurred in the independent practice of midwifery in the great region of Yogyakarta, Indonesia, in 2020. Results: The study found that the things that make respondents anxious in the face of this IUD insertion are experience, information, knowledge, and family support. The quantitative analysis found different pain levels in the VR and non-VR groups (t118 = 1,65, p < 0,001). Conclusions: VR can be used as a method to distract clients during IUD insertion.